Cytospora berberidicola sp. nov. (Diaporthales, Cytosporaceae) in China - Liu, Yun; Chi, Bao-Jie; Jiang, Ning; Yang, Xiang-Li; Liu, Jin (Phytotaxa, 2023)
Several Cytospora species have been identified as pathogens that cause canker diseases. In this study, we examined the causal agent of stem canker on Berberis thunbergii var. atropurpurea in Tibet, China. Three fungal strains were isolated that exhibited morphological characteristics consistent with Cytospora, displaying hyaline and allantoid conidia. Differentiation of species within this genus primarily relies on morphology and molecular data. A new species, Cytospora berberidicola, is introduced based on morphology and molecular data of combined ACT, ITS, RPB2, TEF1 and TUB2 sequences.